Phenotyping, genetics and ‘-omics’ approaches to unravel and introgress enhanced resistance against apple scab (Venturia inaequalis) in apple cultivars (Malus x domestica) - Švara, Anže; De Storme, Nico; Carpentier, Sebastien; Keulemans, Wannes; De Coninck, Barbara (Oxford University Press, 2024)
Abstract Apple scab disease, caused by the fungus Venturia inaequalis, endangers commercial apple production globally. It is predominantly managed by frequent fungicide sprays that can harm the environment and promote the development of fungicide-resistant strains. Cultivation of scab-resistant cultivars harboring diverse qualitative Rvi resistance loci and quantitative trait loci associated with scab resistance could reduce the chemical footprint. A comprehensive understanding of the host-pathogen interaction is, however, needed to efficiently breed cultivars with enhanced resistance against a variety of pathogenic strains. Breeding efforts should not only encompass pyramiding of Rvi loci and their corresponding resistance alleles that directly or indirectly recognize pathogen effectors, but should also integrate genes that contribute to effective downstream defense mechanisms. This review provides an overview of the phenotypic and genetic aspects of apple scab resistance, and currently known corresponding defense mechanisms. Implementation of recent ‘-omics’ approaches has provided insights into the complex network of physiological, molecular and signaling processes that occur before and upon scab infection, thereby revealing the importance of both constitutive and induced defense mechanisms. Based on the current knowledge, we outline advances towards more efficient introgression of enhanced scab resistance into novel apple cultivars by conventional breeding or genetic modification techniques. However, additional studies integrating different ‘-omics’ approaches combined with functional studies will be necessary to unravel effective defense mechanisms as well as key regulatory genes underpinning scab resistance in apple. This crucial information will set the stage for successful knowledge-based breeding for enhanced scab resistance.